2003
DOI: 10.2355/isijinternational.43.161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gas Composition on the Carbothermic Reduction of Manganese Oxide.

Abstract: This paper examines the reduction of pure MnO, Groote Eylandt (Northern Australia) manganese ore, siliceous manganese fines and ferromanganese slag by graphite. Reduction was conducted in the stagnant atmosphere of argon, Ar-CO gas of varying composition and helium. The rate and extent of reduction were determined by thermo-gravimetric analysis and by monitoring CO and CO 2 concentrations in the gas phase. The rate of MnO reduction in Ar-CO gas increased with decreasing CO partial pressure. Reduction in helium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 3 publications
3
44
0
Order By: Relevance
“…[10,11] It was established that the rate of carbothermal reduction of manganese ore is faster in helium than in argon [10,11] and faster in hydrogen than in helium. [11] This was explained by the higher diffusion coefficient of CO in helium and hydrogen in comparison with argon (by a factor of 4) and by involvement of hydrogen in the reduction process.…”
Section: Carbothermal Reduction Of Titania In Different Gas Atmosphermentioning
confidence: 99%
“…[10,11] It was established that the rate of carbothermal reduction of manganese ore is faster in helium than in argon [10,11] and faster in hydrogen than in helium. [11] This was explained by the higher diffusion coefficient of CO in helium and hydrogen in comparison with argon (by a factor of 4) and by involvement of hydrogen in the reduction process.…”
Section: Carbothermal Reduction Of Titania In Different Gas Atmosphermentioning
confidence: 99%
“…Hence, it has been proposed that the carbothermic reduction of MnO is a mixed-control reaction that controls both the chemical reaction and the CO mass transfer in the gas phase. [12] The mechanism of MnO reduction from low and high MnO containing slags by the dissolved carbon in liquid iron is also well known. [3,5,6,10] According to this mechanism, MnO is reduced by Fe at the slag/metal interface and Mn and FeO are produced.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] These studies have been mainly conducted in graphite crucibles with or without an initial metal phase. Stirring has no significant effect on the kinetics of MnO reduction, whereas the reduction rate is affected by the slag composition and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Authors of works 3,5,[7][8][9][10][11][12] concluded that lowering CO partial pressure increases both the rate and extent of reduction. The fastest rate of carbothermal manganese ore reduction was achieved in inert atmosphere.…”
Section: Introductionmentioning
confidence: 99%